Physicochemical Properties Of 131I-Rutin Under Acidic Labeling Condition As A Radiolabeled Compound For The Diagnosis Of Cancer - Maula Eka Sriyani; Maudy Shintia; endah rosyidiah; Witri Nuraeni; Adinda Saraswati; Eva Maria Widyasari (Jurnal Sains dan Teknologi Nuklir Indonesia (Indonesian Journal of Nuclear Science and Technology), 2021)
Radiolabeled rutin (131I-rutin) has potential use in future diagnosis of cancer. The physicochemical characteristics of 131I-rutin are essential in regard to its distribution and accumulation in the body. Therefore, to ensure successful delivery of a labeled compound, it is necessary to evaluate its physicochemical properties. The labeling of 131I-rutin was accomplished using the oxidation method assisted by Chloramine-T under acidic conditions. Radiochemical purity value was measured by thin-layer chromatography (TLC-SG F254) using 100% methanol as the mobile phase. The electrical charge of 131I-rutin was determined by the paper electrophoresis. Moreover, the lipophilicity (P) was evaluated by the partition coefficient in the organic-water liquid. Plasma protein binding was determined in vitro by precipitation method using a 5% trichloroacetic acid (TCA) solution. The results showed that 131I-rutin has a neutral charge and a lipophilicity value (Log P) of 0.395 ± 0.203 (hydrophilic), and was bound to human blood plasma proteins with a percentage of 69.36% ± 1.88%.